D-dimer rise in outpatients with COVID 19 and comorbidities - Miljković Ana R. (Serbian Medical Society, Belgrade, 2021)
Introduction: COVID-19 is an infectious disease caused by a newly discovered Coronavirus. Most of the infected people will go through it with mild to moderate respiratory symptoms and recover without any specific treatment. Older people and people with medical issues, such as cardiovascular diseases, diabetes, chronic pulmonary diseases, malignant diseases are at higher risk for the severe form of the disease. Case report: Female patient, 57, physician, presents with symptoms of Sars-Cov-2 virus infection. Her personal history is significant for pulmonary thromboembolism (PTE). This is a disease which should be paid special attention to. Conclusion: A new Coronavirus infection, which struck the world a year ago, presents a great challenge for general physicians (GPs) and the health system as a whole. The scientific and medical community and the general public must lean on verified facts in this fight against the COVID-19 pandemic. They should be ready to change their treatment protocols, as new information appears from properly designed, implemented, and presented basic and clinical studies. Each patient should be approached with special care, using up-todate facts and proofs from clinical practice, and guided by the newest treatment protocols thus reducing complications in COVID-19 patients with comorbidities.